Lessons Learned in Community Based Service Learning Results of Year One a Synthesis - Oracion, Enrique G. (Silliman Journal, 2022)
This article is a synthesis of the results of the community-based service-learning program of Silliman University during its first ear of implementation. An interdisciplinary group of students and faculty collaborated to realize the program's vision and mission according to a project design. Because several activities were undertaken in the community, coordination, monitoring, and supervision to achieve the desired results were imperative. Documentation of operation and evaluation of the results were carried out while the experiences of the students upon which they were expected to reflect upon the values they have learned were processed. Results of the first year of operation show a number of ideal practices that need to be developed for the conduct of service-learning to fully succeed. First, participants must have commitmeht and dedication; second, the program must be participatory; third, it must be process-oriented and goal-directed; fourth, it must aim for community empowerment,. and fifth, it must instill social responsibility among students. Finally, it is important for the program to aim to be sustainable.